Marker‐assisted breeding for improvement of anaerobic germination in japonica rice (Oryza sativa) - Kim, Suk-Man; Kim, Choon-Song; Jeong, Ji-Ung; Reinke, Russell F.; Jeong, Jong-Min (Wiley, 2019)
Direct seeding is increasingly being practiced in rice cultivation areas because it saves labour and reduces cost of production and management. In this study, four japonica‐type breeding lines were developed from a cross of a japonica cultivar and an AG‐tolerant donor, KHO, using marker‐assisted selection. Validation of the target genes AG1 and AG2 in the selected lines was examined by PCR analysis and the background recovery rate by the recurrent parent was confirmed by genotyping using a 6K SNP chip. Compared to the recurrent, the survival rates of the selected lines were improved in a range from 33% to 115% in three conditions; in particular, the survival rate was increased in more than twice that of the recurrent parent under the hypoxic condition. The main agronomic trait, yield and quality‐related traits were similar to those of the recurrent parent. The use of these lines will contribute to the expansion of the cultivation area due to the proven economic benefits of direct seeding in Korea.